2018
DOI: 10.1016/j.ijimpeng.2018.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigations into SGP laminated glass under low velocity impact

Abstract: Link to publication on Research at Birmingham portal General rights Unless a licence is specified above, all rights (including copyright and moral rights) in this document are retained by the authors and/or the copyright holders. The express permission of the copyright holder must be obtained for any use of this material other than for purposes permitted by law. • Users may freely distribute the URL that is used to identify this publication. • Users may download and/or print one copy of the publication from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Similar conclusion was reached by Overend et al in [4] for laminated glass beams under quasi-static bending, where the post-fracture bearing capacity of tested multi-layer laminated glass units was significant and also exceeded in some cases the strength at first fracture. In [39], the authors also reported an improvement in post-breakage stiffness of samples with heat strengthened glass layers compared to fully tempered glass layers due to their beneficial fragmentation pattern. Further, experimental results in [40] confirmed that the annealed glass plies provided the highest resistance in the post-breakage phase.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Similar conclusion was reached by Overend et al in [4] for laminated glass beams under quasi-static bending, where the post-fracture bearing capacity of tested multi-layer laminated glass units was significant and also exceeded in some cases the strength at first fracture. In [39], the authors also reported an improvement in post-breakage stiffness of samples with heat strengthened glass layers compared to fully tempered glass layers due to their beneficial fragmentation pattern. Further, experimental results in [40] confirmed that the annealed glass plies provided the highest resistance in the post-breakage phase.…”
Section: Introductionmentioning
confidence: 93%
“…Limited amount of works can also be found for the impact response of multi-layer laminated glass in the last decade, identifying the critical impact load for laminated glass panels with a few broken glass layers. Wang et al pointed out, in their experimental study on lowvelocity impact resistance of multi-layer glass panels [39], that the peak impact force at the second breakage was in some cases larger than that at the first breakage. Similar conclusion was reached by Overend et al in [4] for laminated glass beams under quasi-static bending, where the post-fracture bearing capacity of tested multi-layer laminated glass units was significant and also exceeded in some cases the strength at first fracture.…”
Section: Introductionmentioning
confidence: 99%
“…In the 2000's, theoretical [ [20] , [21] , [22] , [23] , [24] , [25] , [26] ], numerical [ [28] , [29] , [30] , [31] , [32] ] and experimental [ [33] , [34] , [35] , [36] ] researches on the actual behavior of laminated glass further enhaced. Researches showed that structural behavior of laminated glass stands among two limiting cases which are layered and monolithic cases [ 2 , 7 , 8 , 19 ]…”
Section: Previous Researchmentioning
confidence: 99%
“…Numerical attempts using combined Voronoi tessellation and finite-discrete element method were also carried out by Wang et al to investigate the influence of fracture pattern on the stiffness and resistance of fractured tempered glass laminates [13] and beam [14]. The findings so far reveal that the residual resistance of fractured glass is also highly related to the interlayer and adhesion properties [15]. For example, a stiffer interlayer or higher adhesion level will limit the volume expansion of tempered glass fragments at breakage point and hence facilitate integrity of glass layer.…”
Section: Introductionmentioning
confidence: 99%